Lumiliximab in chronic lymphocytic leukemia (Hematology Meeting Reports, 2009)
Lumiliximab is an anti-CD23 monoclonal antibody that is being investigated for the treatment of relapsed B-cell CLL. CD23 is a glycoprotein expressed on the majority of CLL cells. Preclinical data shows synergy of lumiliximab with both fludarabine and rituximab.1 Lumiliximab monotherapy given weekly or thrice weekly for 4 weeks to patients with relapsed CLL was well tolerated, achieved sustainable CD23 receptor occupancy and showed clinical activity.2 A decrease in ALC was seen in 91% of patients; decrease in lymph node bulk was noted in 52%. A Phase I/II, multiceneter study was conducted to evaluate the safety and efficacy of lumiliximab in combination with fludarabine, cyclophosphamide, and rituximab (L+FCR) for patients with relapsed CLL. Correlative studies included CD23 receptor occupancy on CLL cells, possible effects of elevated serum CD23, relationship of response to baseline presence of CD38 and ZAP 70 (negative prognostic markers), CD55 and CD59 (potential resistance markers to rituximab).3-5 Thirty-one pts with relapsed CLL received either 350 mg/m2 (n=3) or 500 mg/m2 (n=28) of L + FCR (Fludarabine 25 mg/m2/day x 3, cyclophosphamide 250 mg/m2/day x 3, rituximab 375 mg/m2 x 1 on cycle 1 and 500 mg/m2 x 1 on subsequent cycles) for up to six 28-day cycles. All pts completed treatment and follow-up is ongoing. Median age at study entry was 58 yrs, 71 % had Rai stage I/II disease, and the median number of prior regimens was 2 (1-10). Using NCI-WG criteria, overall response rate was 65% complete response (CR) 52% and partial response (PR) 13%.